2015
DOI: 10.1007/s00213-015-3993-z
|View full text |Cite
|
Sign up to set email alerts
|

Operant ethanol self-administration increases extracellular-signal regulated protein kinase (ERK) phosphorylation in reward-related brain regions: selective regulation of positive reinforcement in the prefrontal cortex of C57BL/6J mice

Abstract: Rationale Extracellular-signal regulated protein kinase (ERK1/2) is activated by ethanol in reward-related brain regions. Accordingly, systemic inhibition of ERK1/2 potentiates ethanol reinforcement. However, the brain region(s) that mediate this effect are unknown. Objective To pharmacologically inhibit ERK1/2 in the medial prefrontal cortex (PFC), nucleus accumbens (NAC) and amygdala (AMY) prior to ethanol or sucrose self-administration, and evaluate effects of operant ethanol self-administration on ERK1/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 77 publications
8
38
0
Order By: Relevance
“…In the present study, we found that propofol, as a positive reinforcer, maintained the intravenous self-administration, and increased the expression of p-ERK in the NAc. These results are consistent with several previous studies showing increased p-ERK expression in the NAc following cocaine and ethanol self-administration [16,20,29]. Thus, the data indicated that activation of ERK transduction pathways in the NAc is involved in propofol self-administration.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found that propofol, as a positive reinforcer, maintained the intravenous self-administration, and increased the expression of p-ERK in the NAc. These results are consistent with several previous studies showing increased p-ERK expression in the NAc following cocaine and ethanol self-administration [16,20,29]. Thus, the data indicated that activation of ERK transduction pathways in the NAc is involved in propofol self-administration.…”
Section: Discussionsupporting
confidence: 93%
“…In line with the possible role of ERK1/2 as stop-pathway molecules, systemic inhibition of MKK, the upstream activator of ERK1/2 (Fig. 2), increases moderate and excessive alcohol intake in mice (AS-OSA and 20%LA models) 105, 106, 107 , suggesting that alcohol-induced activation of ERK1/2 is required for keeping consumption under control.…”
Section: Stop Pathways Gate Drinkingsupporting
confidence: 55%
“…Moreover, pretreatment with an inhibitor of ALK, TAE684 (Galkin et al, 2007), prevents the ethanol-induced activation of ERK. As ERK has been shown by several groups to modulate ethanol-related behaviors (Agoglia et al, 2015; Faccidomo, Besheer, Stanford, & Hodge, 2009; Faccidomo, Salling, Galunas, & Hodge, 2015), these latest findings point toward a possible biochemical mechanism for ALK’s influence on ethanol consumption.…”
Section: Strategy For Target Validation Using Accumbal Plasticitymentioning
confidence: 63%